THE ANALYSIS OF THE COMPANIES PROFITABILITY LEVEL EITHER BEFORE OR AFTER THE MERGER (Case Study Upon 7 Open Companies in 2012) - Lala Intan Gemala Sari; Dwi Asih Surjandari (STIE Binaniaga, 2017)
This study aims to analyze the profitability of companies before and after merger. The study of the population is the registered companies in Indonesia Stock Exchange in 2012. Having applied technical purposive sampling, finally this study has selected 7 companies as the research samples. The level of profitability of companies assessed using the Return On Asset (ROA), Return On Investment (ROI), Return On Equit (ROE), Earning Per Share (EPS). Observation period of this study is one year before and one year after merger. Statistic test used is normality one sample test. The result determined that there had not been any increasing of the ROA of the companies happened after the merger. However, the ROE, ROI and EPS had been increased.Keywords: merger, acquisition, profitability ratio.